ERADICATING POVERTY AND HUMAN CAPITAL DEVELOPMENT IN INDONESIA: An Approach with Multilevel Logistic Regression Model - Suryana Suryana; Kadek Swarniati (UIN Sunan Kalijaga Yogyakarta, 2021)
This study investigated the socio-economic determinants at the individual and contextual level of household poverty in Indonesia. The data used in this study is drawn from the March 2020 Indonesia-National Socio-Economic Survey (Susenas) provided by BPS, Statistics-Indonesia. The data were analyzed using the Multilevel Logistics Regression Model. This study indicates that the achievement of the Human Development Index at the provincial level affects the reduction of the poor at the household level. Moreover, at the individual level, household size, education level, and employment status of the household head significantly affect household poverty. The results of this study underscore the need to look beyond the influence of individual-level factors in addressing regional variations in household poverty in Indonesia. Therefore, Government policies to increase human development in provinces with low HDI are needed.